Каркасный анализ предметной области: стационарные динамические задачи теории упругости для изотропных сред с произвольными неоднородностями - Панченко, Б.Е.; Назаренко, А.М. (Кибернетика и системный анализ, 2013)
Розглянуто загальну схему каркасного аналізу предметної області, яка описує широкий клас задач динамічної теорії пружності, що дозволяє розробити інструментальний програмний засіб синтезу застосувань (CASE-засіб) чисельного паралельного високоточного розв язання цього класу задач. Наведено схему високоточного паралельного розв язання систем сингулярних інтегральних рівнянь, які виникають при дослідженні задач дифракції пружних гармонійних хвиль на системах неоднорідностей довільного поперечного перетину. Наведено нові результати обчислень. We present a general scheme of framework analysis of the subject domain that describes a wide class of problems of the dynamic elasticity theory, which allows developing a software tool for the synthesis of applications (CASE-method) of the numerical high-precision parallel solution of this class of problems. We propose a scheme of the high-precision parallel solution to systems of singular integral equations (SIE) that occur in the analysis of certain problems of diffraction of elastic harmonic waves on systems of discontinuities of an arbitrary cross-section. New numerical results are presented.